Assessment of the three ordering processes of Mcdonald's - Abuan, Jorrie May S. Anacleto, Erha Jane M. Avinante, Ma. Kayla Joei S. Baliad, Norvic John B. Baltazar, Bernadine Ann B. Bautista, Nathalie Jone D. Gonzaga, Alessandra Joechel. Peralta, Kyrztal Joy R. 4 0 16; 5
Abstract The study aimed to determine which method of taking orders at Mcdonald's is the most effective. The researchers conducted this study to determine how effective are the following ordering processes in terms of Convenience, Ordering Speed, and Accessibility. The selected respondents for this study are random customers from Metro Manila and selected cities in Cavite. The researchers discovered that in the category of convenience, respondents considered mobile apps to be the most convenient. However, in the other two categories, accessibility and speed, respondents find the counter to be the most favorable, with 3.297297 and 2.864865, respectively, among the three-ordering ways.
Business Research : (BSBA major in Operations Management) - Pamantasan ng Lungsod ng Maynila, 2022
Keywords: 2 -- 0; 6; 20; 20; 2